Nasal airflow simulations suggest convergent adaptation in Neanderthals and modern humans - de Azevedo, Soledad; González, M. F.; Cintas, Celia; Ramallo, Virginia; Quinto Sanchez, Mirsha Emmanuel; Marquez, Federico; Hünemeier, Tábita; Paschetta, Carolina Andrea; Ruderman, Anahí; Navarro, Jose Pablo; Pazos, Bruno Alfredo; Silva de Cerqueira, Caio Cesar; et al. (Proceedings of the National Academy of Sciences)
Both modern humans (MHs) and Neanderthals successfully settled across western Eurasian cold-climate landscapes. Among the many adaptations considered as essential to survival in such landscapes, changes in the nasal morphology and/or function aimed to humidify and warm the air before it reaches the lungs are of key importance. Unfortunately, the lack of soft-tissue evidence in the fossil record turns difficult any comparative study of respiratory performance. Here, we reconstruct the internal nasal cavity of a Neanderthal plus two representatives of climatically divergent MH populations (southwestern Europeans and northeastern Asians). The reconstruction includes mucosa distribution enabling a realistic simulation of the breathing cycle in different climatic conditions via computational fluid dynamics. Striking across-specimens differences in fluid residence times affecting humidification and warming performance at the anterior tract were found under cold/dry climate simulations. Specifically, the Asian model achieves a rapid air conditioning, followed by the Neanderthals, whereas the European model attains a proper conditioning only around the medium-posterior tract. In addition, quantitative-genetic evolutionary analyses of nasal morphology provided signals of stabilizing selection for MH populations, with the removal of Arctic populations turning covariation patterns compatible with evolution by genetic drift. Both results indicate that, departing from important craniofacial differences existing among Neanderthals and MHs, an advantageous species-specific respiratory performance in cold climates may have occurred in both species. Fluid dynamics and evolutionary biology independently provided evidence of nasal evolution, suggesting that adaptive explanations regarding complex functional phenotypes require interdisciplinary approaches aimed to quantify both performance and evolutionary signals on covariation patterns. Fil: de Azevedo, Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro ...